Improvements to water purification and sanitation infrastructure may reduce the diarrheal burden in a marginalized and flood prone population in remote Nicaragua - Wurzelmann Daniel; Peña Rodolfo; Horney Jennifer; Edwards Jess; Denslow Sheri A; Morgan Douglas (BMC, 2010)
Abstract Background The isolated northern region of Nicaragua has one of the highest rates of diarrheal disease in Central America. Political and environmental hardships faced by inhabitants of this region are contributing factors to this health inequity. The aim of this study was to assess the relationship between water and latrine infrastructure and the prevalence of diarrhea in this region. Methods A population-based, cross-sectional survey of women of reproductive age was conducted in the Sahsa region of northern Nicaragua in July, 2009. Households were selected by two stage cluster sampling methodology. A questionnaire was administered in Spanish and Miskito with assessment of household and socioeconomic conditions, sanitation practices, and health care access. Diarrhea prevalence differences at the household level over a two week reporting period were estimated with a standardized instrument which included assessment of water treatment and latrine use and maintenance. Results There were 189 women enrolled in the current study. The use of water purification methods, such as chlorine and filters, and latrine ownership were not associated with reduced prevalence of household diarrhea in the two week reporting period. Latrine overflow, however, was associated with an increased prevalence of diarrhea during the same two week period [adjusted prevalence difference and 95% CI: 0.19 (0.03, 0.36)]. Conclusions Simple, low cost interventions that improve water and latrine infrastructure may reduce the prevalence of diarrheal disease in the isolated regions of Nicaragua and Central America.